2021
DOI: 10.1111/dom.14315
|View full text |Cite
|
Sign up to set email alerts
|

Fasting oxyntomodulin, glicentin, and gastric inhibitory polypeptide levels are associated with activation of reward‐ and attention‐related brain centres in response to visual food cues in adults with obesity: A cross‐sectional functional MRI study

Abstract: Postprandial increases in gastrointestinal hormones are associated with reduced energy intake, partially through direct effects on the brain. However, it remains unknown whether the fasting levels of gastrointestinal hormones are associated with altered brain activity in response to visual food stimuli. We therefore performed a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…To assess a possible correlation between reward responses and ghrelin levels, they limited their analysis to the insula and found no significant correlation in any of the groups (Steele et al, 2015). One study that assessed whole-brain activations did not find any association between fasting ghrelin levels and anticipatory food reward responses (Perakakis et al, 2021). Finally, two other studies found negative correlations with activation in dlPFC, right caudate, limbic and paralimbic regions (Bogdanov et al, 2020; Karra et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess a possible correlation between reward responses and ghrelin levels, they limited their analysis to the insula and found no significant correlation in any of the groups (Steele et al, 2015). One study that assessed whole-brain activations did not find any association between fasting ghrelin levels and anticipatory food reward responses (Perakakis et al, 2021). Finally, two other studies found negative correlations with activation in dlPFC, right caudate, limbic and paralimbic regions (Bogdanov et al, 2020; Karra et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Baseline scores of emotional eating affected the early sensitivity to liraglutide treatment in participants with T2D, and emotional eating was associated with attenuated liraglutide-induced decreases in anticipatory food reward responses in the amygdala, insula, and caudate, as well as attenuated increases in consummatory responses in the insula and caudate (van Bloemendaal et al, 2015b; van Ruiten et al, 2022). However, another study found no significant correlation between endogenous GLP-1 levels and anticipatory activation for food cues (Perakakis et al, 2021). Interestingly, one study reported no correlation between GLP-1 and DLPFC response to food cues, but found that the interaction between GLP-1 levels and DLPFC response robustly predicted body weight change (Maurer et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…To assess a possible correlation between reward responses and ghrelin levels, they limited their analysis to the insula and found no significant correlation in any of the groups (Steele et al, 2015). One study that assessed whole-brain activations did not find any association between fasting ghrelin levels and anticipatory food reward responses (Perakakis et al, 2021). Finally, two other studies found negative correlations with activation in dlPFC, right caudate, limbic and paralimbic regions (Bogdanov et al, 2020;Karra et al, 2013).…”
Section: 1mentioning
confidence: 99%
“…5,6 Further, a 2021 randomized controlled trial using functional magnetic resonance imaging (MRI) showed that high fasting circulating levels of oxyntomodulin were significantly associated with decreased activation of the brain reward system in obese people, providing the strongest evidence to date that the effect of oxyntomodulin on weight loss involves stimulation of the brain. 7 Although the pharmacological effects of oxyntomodulin have mostly been studied in the context of weight loss, several studies have also demonstrated its beneficial effects on improving insulin secretion and glucose metabolism in type 2 diabetes mellitus. 8 Further, investigations of gut peptides (including oxyntomodulin) in individuals with postpancreatitis diabetes mellitus have recently gained momentum.…”
mentioning
confidence: 99%
“…Oxyntomodulin has been shown to cause weight loss in overweight and obese humans by lowering their food intake and increasing their energy expenditure 5,6 . Further, a 2021 randomized controlled trial using functional magnetic resonance imaging (MRI) showed that high fasting circulating levels of oxyntomodulin were significantly associated with decreased activation of the brain reward system in obese people, providing the strongest evidence to date that the effect of oxyntomodulin on weight loss involves stimulation of the brain 7 …”
mentioning
confidence: 99%